Voices of Students who Quit Studies Amidst the Pandemic - Cortes, Venus M.; B. Matugas, Fearlian Mae; C. Soriano, Rain Heart; O. Seniedo, Charlene; A. Julve, Rhena Maureen; P. Tajanlangit, Ricci Mae (International Journal of Humanities and Education Development (IJHED), 2022)
The present study sought to describe and interpret the experiences that became the factor of the students at a selected state university in Cebu City of Bachelor of Special Needs Education to withdraw and quit studies amidst the pandemic. This research used phenomenology research design to achieve in-depth and rich first-person accounts utilizing interpretative phenomenological analysis with four stages in interpreting the data. Given the societal condition, the data gathering was held through personal conversation in Messenger with a sample size of 5. Findings revealed that the majority of the factors experienced by the respondents were about having problems with internet connection and environmental setbacks while being admitted to online learning. Financial difficulty and experiences with mental health issues were also specified from the results that influenced the decision of the respondents to discontinue their studying.